Prospective phase II study of prophylactic low-dose azacitidine and donor lymphocyte infusions following allogeneic hematopoietic stem cell transplantation for high-risk acute myeloid leukemia and myelodysplastic syndrome - Guillaume, Thierry; Malard, Florent; Magro, Leonardo; Labopin, Myriam; Tabrizi, Reza; Borel, Cécile; Chevallier, Patrice; Vigouroux, Stéphane; Peterlin, Pierre; Garnier, Alice; Rubio, Marie-Thérèse; Huynh, Anne; et al. (Bone marrow transplantation (Basingstoke), 2019)
Thirty patients, with high-risk acute myeloid leukemia (AML, n = 20) or myelodysplastic syndrome (MDS, n = 10), were enrolled in a phase II trial entailing prophylactic post-transplant azacitidine (AZA) plus escalated doses of donor lymphocyte infusion (DLI). The median number of AZA cycles was 5 (1–12) with 10 patients (33%) completing the 12 projected cycles. DLI were performed in 17 patients: 5 received one DLI, 2 received 2 DLI and 8 received 3 infusions. AZA was well tolerated, but discontinued in 20 patients primarily due to graft-versus-host disease (GvHD) and relapse. The cumulative incidence (CI) of grade 1–3 acute GvHD was 31.5% and the chronic GvHD CI was 53% at 2 years. At a median follow-up of 49 months (27–63), 18 patients are alive. The overall and disease-free survivals are 65.5% (CI 95% = 48.2–82.8) at 2 years. Cause of death was mainly relapse for 9 patients. The median time to relapse was 7 months (2.5–58) and the cumulative incidence of relapse at 2 years was 27.6% (CI 95% = 12.8–44.6). These results confirm that AZA is well tolerated as a prophylactic treatment to reduce the risk of post-transplantation relapse and compared favorably to those of patients who receive no post-transplant maintenance.